Chest X-Ray Findings in COVID-19 Patients Presenting to Primary Care during the Peak of the First Wave of the Pandemic in Qatar: Their Association with Clinical and Laboratory Findings. (27th October 2021) - Abougazia, Abdelwahed; Alnuaimi, Ahmed; Mahran, Amal; Ali, Tamer; Khedr, Ahmed; Qadourah, Banan; Shareef, Ahmed; Zitouni, Soubhi; Kahveci, Servet; Alqudah, Barham; Al Yassin, Yasser; Eldesoky, Mohamed; et al.
Abstract : When managing coronavirus disease 2019 (COVID-19) patients, radiological imaging complements clinical evaluation and laboratory parameters. We aimed to assess the sensitivity of chest radiography findings in detecting COVID-19, describe those findings, and assess the association of positive chest radiography findings with clinical and laboratory findings. A multicentre, cross-sectional study was conducted involving all primary health care corporation-registered patients (2485 patients) enrolled over a 1-month period during the peak of the 2020 pandemic wave in Qatar. These patients had reverse transcription-polymerase chain reaction-confirmed COVID-19 and underwent chest radiography within 72 hours of the swab test. A positive result on reverse transcription-polymerase chain reaction was the gold standard for diagnosing COVID-19. The sensitivity of chest radiography was calculated. The airspace opacities were mostly distributed in the peripheral and lower lung zones, and most of the patients had bilateral involvement. Pleural effusion was detected in some cases. The risk of having positive chest X-ray findings increased with age, Southeast Asian nationality, fever, or a history of fever and diarrhoea. Patients with cardiac disease, obesity, hypertension, diabetes, and chronic kidney disease were at a higher risk of having positive chest X-ray findings. There was a statistically significant increase in the mean serum albumin, white blood cell count, neutrophil count, and serum C-reactive protein, hepatic enzymes, and total bilirubin with an increase in the radiographic severity score.